Conditions of labour in Indian agriculture - Chattopadhyay, Manabendu (Calcutta, 1985)
This book is an outcome of researches on labour conditions and relations in Indian agri culture carried out during the years 1975 to 1981 by the author. It is felt that a concrete study of the agricultural labour class which constitutes a major category in relation to the other agrarian class categories would be useful for an understanding of the class dynamics vls-a-vis the problems of poverty and inequality in our rural society. The studies presented here reveal that certain widely accepted ideas regarding the role of labour in agriculture do not stand critical empirical scrutiny. The present effort attempts a positive approach towards the building up of new analytical frameworks designed to tackle many of the problems in the analysis of lobour conditions and relations. It is hoped that the book will be found useful for teaching at higher levels of university education where agricultural economics is taught as a subject of specialisa tion.
Keywords: Labour and laboruing classes